2020
DOI: 10.18203/2320-1770.ijrcog20205769
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of centchroman and PPIUCD in terms of efficacy, safety and continuation rate in immediate postpartum period

Abstract: Background: Study was done to assess the efficacy, safety and continuation rate of Centchroman and IUCD administered in immediate postpartum period (within 48 hours).Methods: An interventional study was conducted in Obstetrics and Gynecology department of Safdarjung Hospital, New Delhi, at a tertiary care hospital after approval from ethical committee. 280 women were enrolled in the study and divided into 2 groups centchroman group and PPIUCD group, 140 in each group after excluding the exclusion criteria and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Centchroman was introduced into the family planning basket of contraceptives but is underutilised as a postpartum spacing method despite its safety and convenient dosing schedule. Recent studies have demonstrated that centchroman has higher satisfaction and continuation rates than postpartum intrauterine devices and progesterone-only pills [1,4]. No untoward side effects have been reported with centchroman use till now [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Centchroman was introduced into the family planning basket of contraceptives but is underutilised as a postpartum spacing method despite its safety and convenient dosing schedule. Recent studies have demonstrated that centchroman has higher satisfaction and continuation rates than postpartum intrauterine devices and progesterone-only pills [1,4]. No untoward side effects have been reported with centchroman use till now [2].…”
Section: Discussionmentioning
confidence: 99%
“…There are very few studies available regarding the acceptance rates of centchroman in India. The acceptance rates widely range from 60 to 77.5% [1,4]. However, no literature exists on the contraceptive acceptance rate of centchroman in the postpartum period.…”
Section: Introductionmentioning
confidence: 99%